Developing focal construct technology for in vivo diagnosis of osteoporosis. (January 2019) - Greenwood, C; Rogers, K; Wilson, M; Lyburn, I; Evans, P; Prokopiou, D
Abstract: Osteoporosis is a prevalent bone disease around the world, characterised by low bone mineral density and increased fracture risk. Currently, the gold standard for identifying osteoporosis and increased fracture risk is through quantification of bone mineral density (BMD), using dual energy X-ray absorption (DEXA). However, the use of BMD to diagnose osteoporosis is not without limitation and arguably the risk of osteoporotic fracture should be determined collectively by bone mass, architecture and physicochemistry of the mineral composite building blocks. Rather than depending exclusively on the 'mass' of bone, our previous research investigated predicting the risk of fracture using 'bone quality'. The work highlighted that the material properties of OP tissue differ significantly to that of 'normal' bone and for the first time reported the clinical value of new biomarkers (obtained from X-ray scatter signatures) for fracture risk prediction. Thus, in order to improve fracture prediction models, diagnostic tools need to be developed which not only measure bone mineral density, but also bone quality. This pilot study builds on our previous work and aims to develop a new technology, Focal Construct Technology (FCT), which is hoped can measure XRD signatures in vivo. Our previous work was performed entirely with interrogating probes applied in transmission mode. This has some disadvantages that would be overcome were reflection mode employed. This study involves the creation of unique, high impact data with the potential to form the basis of a new generation of medical diagnostic instrumentation. A systematic series of conventional reflection mode ex vivo experiments were performed in which bone specimens were examined through increasing thicknesses of overlaying muscle/fat/skin. Further, we applied FCT to these geometries. This had not previously been attempted and required some initial modelling to ensure correct topologies of the hollow beams. The results from this study suggest it may be possible to obtain the parameters in vivo with the same precision as those obtained within the laboratory when using FCT.